Evolution of access control models for protection of patient details: a survey - Sinha, Geetanjali; Shankar K.C, Prabhu; Jain, Shaurya (International Journal of Engineering and Technology, 2018)
Hospitals across the world are adapting to Electronic Hospital Information Systems and are moving away from the manual paper systems to provide patients efficient services. Numerous Access ControlModels have been deployed for securing patient privacy one of them being Role Based Access Control Model (RBAC). The current models merely allow access on the basis of roles and role hierarchy without actually understanding the real intention of the person accessing the system. This could lead to a compromise of patient privacy and thus new methods have been evolving. In this survey we will see an evolution of the access control models which lead to the discovery of KC-RBAC (Knowledge Constrained Role Based Access Control) Model which takes into consideration the knowledge related to the medical domain along with the role to provide authorization.